Relationship Between Breeding Places, 3M Plus Practices, and Insecticide use with Dengue Fever Incidence: A Literature Review - Ferawati, Nour Baeti; Wahyuningsih, Nur Endah; Raharjo, Mursid (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Dengue hemorrhagic fever remains a major public health problem in tropical countries, including Indonesia. Environmental conditions, community behavior, and vector control practices contribute significantly to dengue transmission. Objective: This literature review aimed to analyze the relationship between breeding places, the 3M Plus strategy (draining, covering, reusing, and additional control efforts), and insecticide use with the incidence of dengue fever Method: This study used a systematic literature review approach by searching Google Scholar, PubMed, DOAJ, and Garuda databases for articles published between 2015 and 2025. Studies examining breeding places, 3M Plus practices, and insecticide use in relation to dengue incidence were included. Results and Discussion: Eight studies met the inclusion criteria. Poorly managed water containers and inadequate waste management were associated with increased Aedes aegypti density and dengue incidence. Consistent implementation of 3M Plus practices was associated with reduced larval indices and dengue cases. Insecticide use was effective for short-term control but limited by resistance and improper application. Conclusion: Integrated vector management combining environmental sanitation, consistent 3M Plus practices, appropriate insecticide use, and community education is essential for sustainable dengue prevention.